2016
DOI: 10.3208/jgssp.v04.j04
|View full text |Cite
|
Sign up to set email alerts
|

Examining efficient assisting geotechnology for permeation grouting of ultra microfine cement for soil liquefaction countermeasure

Abstract: The development of ground improvement technology by means of permeation grouting using recently developed ultra microfine cement has been underway by the authors' group, especially for mitigating effects of soil liquefaction on existing structures built on liquefiable soil deposits. From the experiences gained from the field tests carried out at the different two sites, this method works well for relatively clean fine sand deposits, though it may still need some refinement for silty sand deposits. Some supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In addition, the authors conducted field injection tests and laboratory model experiments on ultra-fine particle cement, and showed that this improved material is effective for sand ground containing fine particles (e.g. Weihong et al (2016) and Hashimoto et al(2019)). However, it have not studied much about the dynamic behavior during earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors conducted field injection tests and laboratory model experiments on ultra-fine particle cement, and showed that this improved material is effective for sand ground containing fine particles (e.g. Weihong et al (2016) and Hashimoto et al(2019)). However, it have not studied much about the dynamic behavior during earthquakes.…”
Section: Introductionmentioning
confidence: 99%